Evaluation Of Midwives' Compliance In Implementing The Principles Of Respectful Maternity Care In Antenatal Care Services At Community Health Centers - Cahyani, Mila; Surani, Endang (Universitas Prima Indonesia, 2025)
This study aims to comprehensively evaluate the level of midwives' compliance in implementing Respectful Maternity Care (RMC) principles in antenatal care (ANC) services at community health centers (Puskesmas), through a systematic and structured literature review approach. The literature search was conducted methodologically by utilizing three main, credible and broad-based scientific databases: Google Scholar, PubMed, and Publish or Perish. The search strategy was formulated using a combination of keywords in Indonesian and English, such as: